2019
DOI: 10.4028/www.scientific.net/ddf.390.99
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silica Nanofluid on CO<sub>2</sub> Mass Transfer and Hydrocarbon Property Alteration in a Carbonated Water-Hydrocarbon System

Abstract: The study investigates the impact of a nanofluid suspended in carbonated water (CW) on the CO2 mass transfer into hydrocarbon in a carbonated water/hydrocarbon system. Furthermore the study addresses into the influence of the nanofluid assisted CO2 mass transfer on the viscosity and density of hydrocarbon and its relevance to enhanced oil recovery (EOR). The experiments were carried out at 10-70 bar at 25°C and 45°C using an axisymmetric drop shape analysis (ADSA) for three concentrations of silica nanofluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…As shown in Figure , the addition of 0.021 and 0.04 wt % nanoparticles to CW led to oil recovery of 50.91% and 48.18%, respectively, significantly surpassing the recovery obtained with conventional CW injection (45.76%). Research conducted by Bagalkot et al also confirmed that nanofluids can increase the CO 2 content in CW and facilitated the mass transfer of CO 2 from water to crude oil . After adding nanofluids, the CO 2 content in water increased by 17%.…”
Section: Enhanced Carbonated Water Injectionmentioning
confidence: 99%
“…As shown in Figure , the addition of 0.021 and 0.04 wt % nanoparticles to CW led to oil recovery of 50.91% and 48.18%, respectively, significantly surpassing the recovery obtained with conventional CW injection (45.76%). Research conducted by Bagalkot et al also confirmed that nanofluids can increase the CO 2 content in CW and facilitated the mass transfer of CO 2 from water to crude oil . After adding nanofluids, the CO 2 content in water increased by 17%.…”
Section: Enhanced Carbonated Water Injectionmentioning
confidence: 99%